Heterotopic abdominal rat heart transplantation as a model to investigate volume dependency of myocardial remodeling - Benke, Kálmán; Ruppert, Mihály; Radovits, Tamás; Szabó, Gábor (Transplantation, 2017)
Heterotopic abdominal rat heart transplantation has been extensively used to investigate ischemic-reperfusion injury, immunological consequences during heart transplantations and also to study remodeling of the myocardium due to volume unloading. We provide a unique review on the latter and present a summary of the experimental studies on rat heart transplantation to illustrate changes that occur to the myocardium due to volume unloading. We divided the literature based on whether normal or failing rat heart models were used. This analysis may provide a basis to understand the physiological effects of mechanical circulatory support therapy.
Gesehen am 11.04.2018